Glossário bilíngue em Libras com registros lexicográficos da área da saúde, evidenciando a saúde da mulher surda no atendimento médico e hospitalar de Manaus - Rodrigues, Viviana Dourado (Brasil, 2025)
This study aims to collect and organize lexicographic records of Libras signs in the health area, highlighting women's health, to meet the communication needs of this public, as well as health professionals and Libras interpreters who work in the medical and hospital context of Manaus. To this end, we sought to develop an online bilingual glossary in Libras, with terminologies used in medical and hospital care with a focus on women's health, which will be made available on YouTube and accessed through links and QR Code. Due to the lack of a glossary with terms used in the area of women's health, this research aims to facilitate communication between patients and health professionals, aiming at a humanized care, focused on the communication needs of people involved in women's health care. Thus, the theoretical foundation was based on studies on public policies (TEIXEIRA, 2010), Libras and Linguistics (GESSER, 2009), Lexicography (ABADDE, 2011), Santos terminology (2017), Linguistic Variation (CASTRO JUNIOR, 2011), Lexicon (BIDERMAN, 2001). This research consists of a bibliographic review and employed a qualitative, descriptive and exploratory approach (MARCONI AND LAKATOS, 2017), with structured and standardized interviews (REIS, 2009), with carefully selected participants. Initially, for the presentation and analysis of results, the following techniques were used: We selected thirty-four terms in Portuguese, which are used in women's health care. Of the terms chosen, twenty-six signs in Libras were identified, but only ten were selected to integrate this work and analyzed morphologically. The final product was uploaded to YouTube, resulting in an online glossary that will serve as a resource to assist sign language users, healthcare professionals and Libras interpreters, as well as society in general.